2014
DOI: 10.1111/bjop.12107
|View full text |Cite
|
Sign up to set email alerts
|

Testing the bi‐dimensional effects of attitudes on behavioural intentions and subsequent behaviour

Abstract: Attitudes are typically treated as unidimensional predictors of both behavioural intentions and subsequent behaviour. On the basis of previous research showing that attitudes comprise two independent, positive and negative dimensions, we hypothesized that attitudes would be bi-dimensional predictors of both behavioural intentions and subsequent behaviour. We focused on health-risk behaviours. We therefore also hypothesized that the positive dimension of attitude (evaluations of positive behavioural outcomes) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 53 publications
7
32
0
Order By: Relevance
“…Of the 330 participants who completed Time 1 questionnaire, 60% completed Time 2 questionnaire and were successfully matched, producing a final sample of N = 198 participants. This completion rate compared extremely favourably with previously published research using a similar design (e.g., Elliott, Brewster, Thomson, Malcolm, & Rasmussen, [Study 3]). Overall, the study ran for 9 months, from July 2014 to March 2015.…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…Of the 330 participants who completed Time 1 questionnaire, 60% completed Time 2 questionnaire and were successfully matched, producing a final sample of N = 198 participants. This completion rate compared extremely favourably with previously published research using a similar design (e.g., Elliott, Brewster, Thomson, Malcolm, & Rasmussen, [Study 3]). Overall, the study ran for 9 months, from July 2014 to March 2015.…”
Section: Methodssupporting
confidence: 85%
“…2 We acknowledge that the separation of the positive and negative prototype favourability ratings is not consistent with how prototype favourability is often treated in other studies in which researchers have used overall measures of prototype favourability that combine the positive and negative ratings. The factor analytic findings presented in the main text, however, demonstrate that the positive and negative prototype favourability items tapped different (positive and negative) components of prototype favourability and the findings are consistent with research into bi-dimensional attitudes, in which positive and negative valences have been shown to be independent of one another (see Conner et al, 2007;Elliott, Brewster, et al, 2015). Additionally, it should be noted that when the analyses reported in the main text were re-run with an overall measure of prototype favourability (the mean of all the positive and negative items), rather than the separate positive and negative prototype favourability measures, the findings and resulting conclusions were the same.…”
Section: Time 2 Measuressupporting
confidence: 77%
“…The likelihood of a behaviour being performed is then held to increase with the extent to which it is evaluated positively rather than negatively (e.g., Fishbein, ). More recently, however, attitudes have been conceptualized as bidimensional predictors of behaviour (Elliott, Brewster, Thomson, Malcolm, & Rasmussen, ; McCartan & Elliott, ). This means that attitudes comprise separate unipolar, positive, and negative dimensions (e.g., ‘For me, speeding is not at all positive to extremely positive’ and ‘For me, speeding is not at all negative to extremely negative’).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research in which attitudes have been treated as bidimensional predictors of behaviour (Elliott, Brewster, et al ., ; McCartan & Elliott, ) has shown that both the positive and negative attitude dimensions independently predict binge‐drinking intentions (Elliott, Brewster, et al ., [studies 1 and 2]), smoking and unhealthy dieting intentions (Elliott, Brewster, et al ., [study 2]), self‐reported speeding behaviour (Elliott, Brewster, et al ., [study 3]), and objectivity measured speeding behaviour (McCartan & Elliott, ). These studies have also shown that the positive dimension of attitude is a significantly stronger predictor of both intentions and subsequent behaviour than is the negative dimension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation